Green Ganesha Chaturthi: The Ritualising and Materialising of a Green Hindu Identity and the Emerging of an Alternative Representation of Ganesha - Deborah De Koning (Religions, 2022)
With the world facing an ecological crisis, Hindus are challenged to reflect on the ways they impact their environment. The last few decades witnessed a rise of theological reflections on Hindu traditions—especially scriptures and concepts (not least by western scholars)—that advocate environmentally friendly perspectives. This stands in sharp contrast with the multiple examples of how Hindu ritual practices cause harm to the environment. Ganesha Chaturthi is a festival that due to the public element of immersion of Ganesha idols, has led to severe pollution of waterbodies. Because of the attention that has been paid to this lately, the festival now calls for ecofriendly alternatives. This article analyses how recently, environmental awareness is ritualized and materialized in the festival of Ganesha Chaturthi. For this, fieldwork was conducted during Ganesha Chaturthi in Chennai and Mumbai in 2022. The focus of the article lies on the ecofriendly material and ritual innovations of the festival—for instance the variety of Ganeshas made of biodegradable materials—and the dynamics of interaction with (alleged) traditions to validate a Green Hindu identity in general and the development of a Green Ganesha in particular.